Interregional integration of wheat markets in Kazakhstan; Interregionale Integration von Weizenmärkten in Kasachstan - Stephan Brosig; Yorbol Yahshilikov (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2005)
Reliable marketing opportunities in both interregional and international trade along with relatively low transportation [and transaction] costs are essential to profitability of wheat production. In this study we have investigated one aspect of the quality of marketing and trade opportunities in the Kazakh wheat sector, that is the extent and nature of integration among regional wheat markets. We applied threshold cointegration technique to assess the co-movement between time series of elevator prices at three grain-trading (and producing) spots in the northern and central parts of the country. Results suggest that markets of two northern grain trading spots (Petropavlovsk and Kokshetau) are closely connected with each other while their connection with Karaganda in central Kazakhstan is much weaker. Here, levelling out of price gaps through arbitrage trade only occurs after a threshold of considerable extent has been surpassed. – – Eine wichtige Voraussetzung für die Wirtschaftlichkeit der Getreideproduktion sind verlässliche Vermarktungswege, die interregionalen und internationalen Handel zu relativ geringen Transport- und Transaktionskosten zulassen. Die Studie behandelt die Integration regionaler Weizenmärkte miteinander und beleuchtet damit, wie reibungslos Getreidehandel zwischen diesen Regionen möglich ist. Mit Hilfe von Verfahren der threshold cointegration analysis werden Zusammenhänge in den Preisentwicklungen zwischen drei wichtigen Handelsplätzen in Nord und Zentralkasachstan untersucht. Die Märkte der beiden nördlichen Marktorte Petropavlovsk und Kokshetau stehen in enger Verbindung zueinander, während sie wesentlich unabhängiger von den Marktentwickungen im zentralkasachischen Karaganda sind. Ein Ausgleich von Preisunterschieden zwischen den nördlichen Märkten und Karaganda findet erst statt, wenn diese Unterschiede einen beträchtlichen Schwellenwert (threshold) übersteigen.
urn:nbn:de:gbv:3:2-3792
Keywords: C22; Q13; 330; Kazakhstan; Price transmission; Market integration; Threshold cointegration; Kasachstan; Preistransmission; Marktintegration; Kointegration